EVALUASI GEOMETRI JALAN ANGKUT TAMBANG DAN RANCANGAN DRAINASE PADA PT. SUMBER ANUGERAH BUANA KABUPATEN SORONG PROVINSI PAPUA BARAT - Petricia J. Etwiory; Bambang Triyanto (INTAN Jurnal Penelitian Tambang, 2018)
Road is one of the important aspects to support transportation activities. Appropriate road geometry can contribute greatly to the safety and smoothness of transport activities. In addition to the road geometry, water can also affect the condition of haul road, from which it can indirectly affect the transportation activities. Therefore,it is important to conduct an evaluation of the haul road geometry condition based on the AASHTO theory, and to design drainage on the road side of the mine. Road geometry at PT. Sumber Anugerah Buana has not suitable yet based on AASHTO theory. This is proven by using the actual result showing that the the width of straight road was 4 - 7,5 meter, and the width of bend road was 5.3 - 5,5 meter. However, according to AASHTO theory, the width of straight road should be 4,850 meter and the width of bend road should be 7,733 meters. So, it is necessary to add width on straight road in segment IJ and in all segment of bend road. The slope of the mine haul road at PT. Sumber Anugerah Buana already has a safe slope of the road, except the A-B segment and D-E segment that are still above the safe condition, which is more than 15%. PT. Sumber Anugerah Buana does not have drainage, so it is necessary to make channel on the first DTH dimension, that is 0,463 meter wide, 0,701 meter deep, and 0,928 meter wide of the channel surface. Meanwhile, the dimension for the second DTH should be 0, 260 meter wide of the channel bottom, 0.395 meter deep of the channel, and 0,522 meters wide of the channel surface.